2017
DOI: 10.1103/physreve.95.052418
|View full text |Cite
|
Sign up to set email alerts
|

Uniform description of polymer ejection dynamics from capsid with and without hydrodynamics

Abstract: We use stochastic rotation dynamics to examine the dynamics of the ejection of an initially strongly confined flexible polymer from a spherical capsid with and without hydrodynamics. The results obtained using SRD are compared to similar Langevin simulations. Inclusion of hydrodynamic modes speeds up the ejection but also allows the part of the polymer outside the capsid to expand closer to equilibrium. This shows as higher values of radius of gyration when hydrodynamics are enabled. By examining the waiting t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Truncating the tail channel of the virion or increasing the solvent temperature accelerates the evolution of ejection [36]. Other effects that are able to affect the ejection include the chain rigidity [34,[37][38][39], the solvent quality [40,41], the hydrodynamics [36,42], the electrostatics [36,43], the pore dimension [44][45][46], and so on. These effects have been the main topics of investigation in the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Truncating the tail channel of the virion or increasing the solvent temperature accelerates the evolution of ejection [36]. Other effects that are able to affect the ejection include the chain rigidity [34,[37][38][39], the solvent quality [40,41], the hydrodynamics [36,42], the electrostatics [36,43], the pore dimension [44][45][46], and so on. These effects have been the main topics of investigation in the past two decades.…”
Section: Introductionmentioning
confidence: 99%
“…The ejection time was deduced to scale asymptotically asat the osmotic driven stage. Simulations, on the other hand, revealed that translocation behaviors can be altered by the details of the escape pore [16,17], the cavity [18,19], the solvent [20,21], the chain stiffness [19,22], etc. Despite of the varieties, universalities can be still traced.…”
mentioning
confidence: 99%
“…In addition to SRD, we use Langevin dynamics (LD) to model solvent in force measurements and polymer packaging due to its superior computational efficiency. In [15] we showed that LD and SRD without hydrodynamics yield similar results. LD follows the Langevin equation…”
Section: B the Solvent And Polymer Dynamicsmentioning
confidence: 57%
“…Using our general simulation model, we will study the ejection process for polymers of different bending rigidity. In our previous studies on capsid ejection of flexible polymers we showed that the ejection dynamics is governed by the force the polymer beads inside the capsid exert on the bead at the pore entrance [14,15]. As will be seen, this result cannot be generalized to semiflexible polymer chains.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation